Modified titanium dioxide and preparation method and application thereof

By modifying titanium dioxide by organic modification first and then inorganic coating, the problems of unmodified titanium dioxide in particle size distribution, dispersion stability, hygroscopicity and photocatalytic activity are solved, and the excellent performance of modified titanium dioxide in 3D printed ceramic materials and the weather resistance of ceramic products are improved.

CN119797911AActive Publication Date: 2025-04-11GUANGDONG HUI YUN TITANIUM IND CORP LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510037260.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

Unmodified titanium dioxide has problems such as uneven particle size distribution, high surface energy, uneven dispersion, strong hygroscopicity, inconvenient storage, and high photocatalytic activity, resulting in shortening of weather resistance and service life of ceramic products.

Method used

The titanium dioxide is modified first and then the inorganic coating is coated. The specific steps include ultrasonic dispersing the titanium dioxide into an aqueous ethanol solution, adding graphene oxide and titanate coupling agent for composite organic modification, and then coating the sodium metaaluminate and sodium silicate solutions to form a uniform and dense coating.

Benefits of technology

Modified titanium dioxide has good dispersion stability, mechanical strength and high temperature resistance, which significantly improves its application performance in 3D printed ceramic materials and the weather resistance and service life of ceramic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235877030000061
    Figure BDA0005235877030000061
  • Figure BDA0005235877030000072
    Figure BDA0005235877030000072
Patent Text Reader

Abstract

The invention relates to modified titanium dioxide and a preparation method and application thereof.The preparation method comprises the following steps that firstly, titanium dioxide is subjected to composite organic modification through graphene oxide and a titanate coupling agent, and composite powder is obtained; and coating the composite powder with a sodium metaaluminate solution and a sodium silicate solution in sequence to obtain the modified titanium dioxide. The modified titanium dioxide has good dispersion stability, mechanical strength and high temperature resistance, and is used for preparing the 3D printing ceramic material, so that the weather resistance of the 3D printing ceramic material can be enhanced, and the service life of the 3D printing ceramic material can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of modified titanium dioxide, and in particular to a modified titanium dioxide and a preparation method and application thereof. Background Art

[0002] There are multiple problems with unmodified titanium dioxide. First, its particle size distribution is uneven and has a large range, which not only affects the hiding power and glossiness of titanium dioxide, but also may cause uneven dispersion in 3D printed ceramic materials, thus affecting the printing effect. Secondly, titanium dioxide has a high surface energy and is easy to agglomerate itself, resulting in reduced dispersion stability, which may weaken the overall stability and printing quality of printed ceramic materials. Furthermore, titanium dioxide has strong hygroscopicity and is easy to absorb moisture in the air and agglomerate, which not only brings inconvenience to storage and transportation, but also affects its use in 3D printed ceramic materials. In addition, unmodified titanium dioxide has strong photocatalytic activity due to its own lattice defects. It is easy to produce active groups with high oxidation ability under sunlight, which may accelerate the oxidative degradation of organic resins in the surrounding environment, thereby shortening the weather resistance and service life of ceramic products. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a modified titanium dioxide having good high temperature stability, chemical stability and wear resistance, and a preparation method and application thereof.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] In a first aspect, the present invention provides a method for preparing a modified titanium dioxide, comprising the following steps:

[0006] S1. Ultrasonic dispersion of titanium dioxide in 75% volume concentration of ethanol aqueous solution to obtain titanium dioxide slurry, adding titanate coupling agent and graphene oxide, and adjusting the pH of the system to 3-4 with glacial acetic acid, heating to 85-95°C and stirring for reaction for 5-6h, centrifuging, washing, vacuum drying and then crushing to obtain composite powder; wherein the titanium dioxide is nano-grade rutile titanium dioxide with a particle size of 50-300nm, the graphene oxide is nano-grade graphene oxide with a single-layer flake size of 50-300nm, and the mass ratio of the titanium dioxide, graphene oxide and titanate coupling agent is (3-5): 1: 1;

[0007] S2. Ultrasonically disperse the composite powder in water to obtain a composite slurry, heat the composite slurry to 80-90°C and then keep it warm, adjust the pH of the system to 6-6.5, add sodium aluminate solution for coating treatment for 1-3h, adjust the pH of the system to 8-8.5, add sodium silicate solution for coating treatment for 1-3h, mature, filter, wash, dry and crush to obtain the modified titanium dioxide.

[0008] Preferably, in step S1, the mass ratio of the titanium dioxide to the ethanol aqueous solution is 1:(2-3).

[0009] Preferably, in step S1, the ultrasonic power is 130-250 W, the ultrasonic temperature is 45-55° C., and the ultrasonic time is 0.8-1.2 h.

[0010] Preferably, in step S1, the speed of the stirring reaction is 300-500 r / min; the drying temperature is 70-80° C. and the drying time is 2-3 h; and the pulverization is performed by using a jet mill to pulverize to a particle size of 0.2-0.5 μm.

[0011] Preferably, in step S2, the ultrasonic power is 130-250 W, the ultrasonic temperature is 45-55° C., and the ultrasonic time is 0.8-1.2 h.

[0012] Preferably, in step S2, the mass ratio of the composite powder to water is 1:(2-3).

[0013] Preferably, in step S2, the mass concentration of the sodium aluminate solution is 10-40 g / L, and the mass ratio of the composite slurry to the sodium aluminate solution is 1:(0.1-1).

[0014] Preferably, in step S2, the mass concentration of the sodium silicate solution is 20-60 g / L, and the mass ratio of the composite slurry to the sodium silicate solution is 1:(0.1-1).

[0015] Preferably, in step S2, the aging temperature is 80-100°C and the aging time is 1-3h; the drying temperature is 70-90°C and the drying time is 1-2h; and the powder is crushed to obtain a powder of 100-200 mesh.

[0016] In a second aspect, the present invention provides a modified titanium dioxide powder prepared by the preparation method of the modified titanium dioxide powder provided in the first aspect.

[0017] In a third aspect, the present invention provides an application of the modified titanium dioxide described in the second aspect in the preparation of 3D printing ceramic materials.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention adopts the method of first organic modification and then inorganic coating to modify titanium dioxide, so that the prepared modified titanium dioxide has good dispersion stability, mechanical strength, and high temperature resistance, and has good application prospects in 3D printing ceramic materials. Specifically, the present invention first adopts graphene oxide and titanate coupling agent to carry out composite organic modification on titanium dioxide, which not only reduces the agglomeration phenomenon of titanium dioxide, improves the dispersion ability of titanium dioxide, enhances the application stability of titanium dioxide, but also further improves the mechanical properties and weather resistance of titanium dioxide; then, the present invention adopts sodium aluminate solution and sodium silicate solution in turn to coat the titanium dioxide after composite organic modification, forming a uniform and dense coating film, which effectively blocks the photochemical points of titanium dioxide, reduces the generation of high oxidation active groups, and further enhances the weather resistance and service life of titanium dioxide. The modified titanium dioxide prepared by the preparation method of the present invention effectively solves the problems existing in the unmodified titanium dioxide, improves its application performance in 3D printing ceramic materials, enhances the weather resistance and service life of 3D printing ceramic materials, and provides strong support for the development of 3D printing ceramic technology. DETAILED DESCRIPTION

[0020] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0021] The sources of the raw materials used in the following examples and comparative examples are as follows:

[0022] Titanium dioxide: rutile titanium dioxide, the manufacturer is Pangang Titanium Industry, model is NR-508L, TiO2 content ≥80%, rutile content ≥98%, average particle size is 0.052μm;

[0023] Isopropyl tri(dioctyl pyrophosphate) titanate: manufacturer: Tianjin Xiensi Biochemical Technology Co., Ltd., model number: I-0308797;

[0024] Graphene oxide: The manufacturer is Zhongke Yueda (Shanghai) Materials Technology Co., Ltd., the form is powder, the average flake size is less than 300nm, the average number of flake layers: the single layer rate is greater than 98%, and the metal impurity content is ≤0.1%;

[0025] Sodium aluminate: manufacturer is Shandong Lier New Materials Co., Ltd., model number is 54#, Na2Al2O4 ≥ 85.0%, Al2O3 ≥ 53.0%, Na2O ≥ 38.0%;

[0026] Powdered sodium silicate (instant sodium silicate); manufacturer: Foshan Zhongfa Water Glass Factory, model 3.0, modulus 3.0, Na2O content 22.0-26.0%, SiO2 content 55.0-66.0%,

[0027] Alumina: Manufacturer: Guangdong Wengjiang Chemical Reagent Co., Ltd., model number: MA00327;

[0028] Zirconium oxide: manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd., model number is PA00898;

[0029] Room temperature Vickers hardness tester: manufacturer is Shenzhen Senyu Instrument Equipment Co., Ltd., model is HV-1000, item number is SY081348133;

[0030] High temperature Vickers hardness tester: manufacturer is Zibo Diye Instrument Equipment Co., Ltd., model is HLT-X7;

[0031] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.

[0032] Example 1

[0033] A method for preparing modified titanium dioxide comprises the following steps:

[0034] S1. Ultrasonic dispersion of titanium dioxide in 75% volume concentration ethanol aqueous solution at 200W and 50°C to obtain titanium dioxide slurry, adding titanate coupling agent and graphene oxide, and adjusting the pH of the system to 3 with glacial acetic acid, heating to 90°C, stirring and reacting at a speed of 400r / min for 5h, centrifuging, washing, vacuum drying at 80°C for 2h, and crushing with a jet mill to obtain a composite powder with a particle size of 0.3μm; wherein the mass ratio of the titanium dioxide to the ethanol aqueous solution is 1:2, the ultrasonic time is 1h, the mass ratio of the titanium dioxide, graphene oxide and titanate coupling agent is 4:1:1, and the titanate coupling agent is isopropyl tri(dioctyl pyrophosphate acyloxy) titanate;

[0035] S2. Ultrasonic dispersion of the composite powder in water at 200 W and 50 ° C to obtain a composite slurry, heat the composite slurry to 80 ° C and keep it warm, adjust the pH of the system to 6, add a sodium aluminate solution with a mass concentration of 30 g / L for coating treatment for 2 hours, then adjust the pH of the system to 8, add a sodium silicate solution with a mass concentration of 40 g / L for coating treatment for 2 hours, mature at 90 ° C for 2 hours, filter, wash with water, vacuum dry at 80 ° C for 1 hour, and crush with a jet mill to obtain a modified titanium dioxide with a particle size of 150 mesh, wherein the mass ratio of the composite powder to water is 1:2, the ultrasonic time is 1 hour, the mass ratio of the composite slurry to the sodium aluminate solution is 1:0.8, and the mass ratio of the composite slurry to the sodium silicate solution is 1:0.6.

[0036] Example 2

[0037] A method for preparing modified titanium dioxide comprises the following steps:

[0038] S1. Ultrasonic dispersion of titanium dioxide in 75% volume concentration ethanol aqueous solution at 130W and 45°C to obtain titanium dioxide slurry, adding titanate coupling agent and graphene oxide, and adjusting the pH of the system to 3 with glacial acetic acid, heating to 85°C, stirring and reacting at a speed of 300r / min for 5h, centrifuging, washing, vacuum drying at 70°C for 3h, and crushing with a jet mill to obtain a composite powder with a particle size of 0.2μm; wherein the mass ratio of the titanium dioxide to the ethanol aqueous solution is 1:2, the ultrasonic time is 1.2h, the mass ratio of the titanium dioxide, graphene oxide and titanate coupling agent is 3:1:1, and the titanate coupling agent is isopropyl tri(dioctyl pyrophosphate acyloxy) titanate;

[0039] S2. Ultrasonic dispersion of the composite powder in water at 130 W and 45 ° C to obtain a composite slurry, heat the composite slurry to 75 ° C and keep it warm, adjust the system pH to 6, add a sodium aluminate solution with a mass concentration of 10 g / L for coating treatment for 3 hours, then adjust the system pH to 8, add a sodium silicate solution with a mass concentration of 20 g / L for coating treatment for 3 hours, mature at 80 ° C for 3 hours, filter, wash with water, vacuum dry at 70 ° C for 2 hours, and use a jet mill to treat to obtain a modified titanium dioxide with a particle size of 100 mesh, wherein the mass ratio of the composite powder to water is 1:2, the ultrasonic time is 0.8 h, the mass ratio of the composite slurry to the sodium aluminate solution is 1:0.1, and the mass ratio of the composite slurry to the sodium silicate solution is 1:0.1.

[0040] Example 3

[0041] A method for preparing modified titanium dioxide comprises the following steps:

[0042] S1. Ultrasonic dispersion of titanium dioxide in 75% volume concentration ethanol aqueous solution at 250W and 55°C to obtain titanium dioxide slurry, adding titanate coupling agent and graphene oxide, and adjusting the pH of the system to 4 with glacial acetic acid, heating to 95°C, stirring and reacting at a speed of 500r / min for 5h, centrifuging, washing, and then vacuum drying at 75°C for 2h, and treating with a jet mill to obtain a composite powder with a particle size of 0.5μm; wherein the mass ratio of the titanium dioxide to the ethanol aqueous solution is 1:3, the ultrasonic time is 0.8h, the mass ratio of the titanium dioxide, graphene oxide and titanate coupling agent is 5:1:1, and the titanate coupling agent is isopropyl tri(dioctyl pyrophosphate acyloxy) titanate;

[0043] S2. Ultrasonic dispersion of the composite powder in water at 250 W and 55 ° C to obtain a composite slurry, heat the composite slurry to 85 ° C and keep it warm, adjust the pH of the system to 6.5, add a sodium aluminate solution with a mass concentration of 10 g / L for coating treatment for 3 hours, then adjust the pH of the system to 8, add a sodium silicate solution with a mass concentration of 20 g / L for coating treatment for 3 hours, mature at 100 ° C for 1 hour, filter, wash with water, vacuum dry at 90 ° C for 1 hour, and crush with a jet mill to obtain a modified titanium dioxide with a particle size of 200 mesh, wherein the mass ratio of the composite powder to water is 1:3, the ultrasonic time is 1.2 h, the mass ratio of the composite slurry to the sodium aluminate solution is 1:1, and the mass ratio of the composite slurry to the sodium silicate solution is 1:1.

[0044] Comparative Example 1

[0045] The difference between Comparative Example 1 and Example 1 is that inorganic coating is performed first, and then organic modification is performed. The specific steps are as follows:

[0046] S1. Ultrasonic dispersion of titanium dioxide in water at 200W and 50°C to obtain titanium dioxide slurry, heat the titanium dioxide slurry to 80°C and keep it warm, adjust the system pH to 6, add a sodium aluminate solution with a mass concentration of 30g / L for coating treatment for 2h, then adjust the system pH to 8, add a sodium silicate solution with a mass concentration of 40g / L for coating treatment for 2h, mature at 90°C for 2h, filter, wash with water, vacuum dry at 80°C for 1h, and crush with a jet mill to obtain coated titanium dioxide with a particle size of 0.3μm, wherein the mass ratio of composite powder to water is 1:2, the ultrasonic time is 1h, the mass ratio of titanium dioxide slurry to sodium aluminate solution is 1:0.8; the mass ratio of titanium dioxide slurry to sodium silicate solution is 1:0.6;

[0047] S2. Ultrasonic disperse the coated titanium dioxide in a 75% volume concentration ethanol aqueous solution at 200 W and 50 ° C to obtain a slurry, add a titanate coupling agent and graphene oxide, and adjust the pH of the system to 3 with glacial acetic acid. After heating to 90 ° C, stir and react at a speed of 400 r / min for 5 hours, centrifuge, wash with water, and vacuum dry at 80 ° C for 2 hours. Grind with a jet mill to obtain a modified titanium dioxide with a particle size of 150 mesh, wherein the mass ratio of coated titanium dioxide to water is 1:2, the ultrasonic time is 1 hour, the mass ratio of coated titanium dioxide, graphene oxide and titanate coupling agent is 4:1:1, and the titanate coupling agent is isopropyl tri(dioctyl pyrophosphate) titanate.

[0048] Comparative Example 2

[0049] The difference between Comparative Example 2 and Example 1 is that: in Comparative Example 2, no graphene oxide is added, and an equal amount of titanate coupling agent is used to make up for the missing amount.

[0050] Comparative Example 3

[0051] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, no titanate coupling agent is added, and an equal amount of graphene oxide is used to make up for the missing amount.

[0052] Comparative Example 4

[0053] The difference between Comparative Example 4 and Example 1 is that the total amount of titanium dioxide, graphene oxide and titanate coupling agent remains unchanged, and the mass ratio of titanium dioxide, graphene oxide and titanate coupling agent is 2:1:1.

[0054] Comparative Example 5

[0055] The difference between Comparative Example 5 and Example 1 is that the total amount of titanium dioxide, graphene oxide and titanate coupling agent remains unchanged, and the mass ratio of titanium dioxide, graphene oxide and titanate coupling agent is 6:1:1.

[0056] Performance Testing

[0057] 1. Acid solubility test

[0058] The modified titanium dioxide of Examples 1-3 and Comparative Examples 1-5 was tested for acid solubility, and the specific method was as follows: 0.2 g of modified titanium dioxide was added to 10 mL of sulfuric acid with a mass concentration of 98%, ultrasonically dispersed for 1 minute, and then dissolved at 180 ° C for 1 hour. After taking out the sample and cooling it to room temperature, add water to make the volume 100 mL, filter, take 10 mL of the filtrate with a pipette, add 10 mL of hydrogen peroxide solution with a mass concentration of 30%, and dilute to 100 mL with sulfuric acid solution with a mass concentration of 10%. After standing for 1 hour, the absorbance of the solution was tested at 400 nm, and the amount of titanium dioxide dissolved in the corresponding modified titanium dioxide was calculated with reference to the standard curve. See Table 1 for details.

[0059] Table 1 Acid solubility of modified titanium dioxide samples

[0060]

[0061]

[0062] 2. High temperature resistance test

[0063] Ceramic materials for 3D printing are prepared, and the specific formula is as follows: 15 parts by mass of a mixed powder of aluminum oxide and zirconium oxide and 10 parts by mass of modified titanium dioxide (Examples 1-4, Comparative Examples 1-5); wherein the preparation method of the mixed powder of aluminum oxide and zirconium oxide is as follows: aluminum oxide and zirconium oxide with a mass ratio of 1.5:1 are soaked in 75% alcohol, and then placed in a planetary ball mill for vacuum crushing, wherein the mass ratio of steel balls to mixed powder is 4:1, and insulating tape is wrapped to prevent static electricity. The rotation speed is 200 rpm, and the ball milling is performed for 4 hours. The powder after ball milling is dried at 80°C to dry out all moisture and then agglomerate; after simple grinding treatment, a 100-mesh sieve is used for filtration to obtain a mixed powder of zinc oxide and zirconium oxide.

[0064] Each group of 3D printing ceramic materials was fed into the SLM printer for laser 3D printing. Laser 3D printing process parameters: laser power was set to 150W, scanning rate was 1200m / s, scanning spacing was 0.1mm, substrate preheating temperature was 200℃, layer thickness was 30μm, and laser spot diameter was 70μm. A 3D printed workpiece with a rectangular size of 10mm×10mm×12mm was obtained. At the same time, in order to increase the stability of the sample on the substrate, the first layer was set to print twice.

[0065] The printed workpieces of each group were placed in a room temperature (25±5℃) and heated at 500℃ for 1h to test their hardness. The room temperature hardness was measured using a Vickers hardness tester, and the 500℃ hardness was measured using a high temperature Vickers hardness tester. The specific data are shown in Table 2.

[0066] Table 2 Hardness data of printed workpieces at room temperature and 500℃

[0067]

[0068] It can be seen from Table 1 that the acid solubility of the modified titanium dioxide in Examples 1-4 is significantly lower than that of the modified titanium dioxide in Comparative Examples 1-5, indicating that the modified titanium dioxide prepared by the preparation method of the present invention forms a relatively uniform and dense coating layer, thereby reducing the photocatalytic activity of titanium dioxide and helping to improve the weather resistance of 3D printed ceramic materials.

[0069] It can be seen from Table 2 that the mechanical strength of the modified titanium dioxide in Examples 1-4 at room temperature and high temperature is better than that of the modified titanium dioxide prepared in Comparative Examples 1-5, indicating that the modified titanium dioxide prepared by the preparation method of the present invention has excellent mechanical properties and weather resistance.

[0070] By comparing the results of Example 1 and Comparative Example 1 in Table 1-2, it can be seen that the order of organic modification and inorganic coating cannot be changed, and changing the preparation steps may lead to poor performance of the modified titanium dioxide.

[0071] By comparing the results of Example 1 and Comparative Examples 2-3 in Table 1-2, it can be seen that titanium dioxide, graphene oxide and titanate coupling agent have a synergistic effect, which can effectively improve the weather resistance of titanium dioxide and the strength, weather resistance and high temperature resistance of the corresponding workpiece.

[0072] By comparing the results of Example 1 and Comparative Examples 4-5 in Table 1-2, it can be seen that when the mass ratio of titanium dioxide, graphene oxide and titanate coupling agent is (3-5):1:1, the strength, weather resistance and high temperature resistance of the modified titanium dioxide are all at a relatively good level.

[0073] In summary, the modification of titanium dioxide by first organic modification and then inorganic coating not only effectively solves the problems existing in unmodified titanium dioxide, but also improves its application performance in 3D printing ceramic materials, enhances the overall stability and weather resistance of ceramic products, and provides strong support for the development of 3D printing ceramic technology.

[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing modified titanium dioxide, characterized in that: The following steps are involved: S1. Ultrasonic dispersion of titanium dioxide in 75% volume concentration of ethanol aqueous solution to obtain titanium dioxide slurry, adding titanate coupling agent and graphene oxide, and adjusting the pH of the system to 3-4 with glacial acetic acid, heating to 85-95°C and stirring for reaction for 5-6h, centrifuging, washing, vacuum drying and then crushing to obtain composite powder; wherein the titanium dioxide is nano-grade rutile titanium dioxide with a particle size of 50-300nm, the graphene oxide is nano-grade graphene oxide with a single-layer flake size of 50-300nm, and the mass ratio of the titanium dioxide, graphene oxide and titanate coupling agent is (3-5): 1: 1; S2. Ultrasonically disperse the composite powder in water to obtain a composite slurry, heat the composite slurry to 80-90°C and then keep it warm, adjust the pH of the system to 6-6.5, add sodium aluminate solution for coating treatment for 1-3h, adjust the pH of the composite system to 8-8.5, add sodium silicate solution for coating treatment for 1-3h, mature, filter, wash, dry and crush to obtain the modified titanium dioxide.

2. The method for preparing modified titanium dioxide according to claim 1, characterized in that: In the step S1, the mass ratio of the titanium dioxide to the ethanol aqueous solution is 1:(2-3).

3. The method for preparing modified titanium dioxide according to claim 1, characterized in that: In the step S1, the ultrasonic power is 130-250 W, the ultrasonic temperature is 45-55° C., and the ultrasonic time is 0.8-1.2 h.

4. The method for preparing modified titanium dioxide according to claim 1, characterized in that: In the step S1, the speed of the stirring reaction is 300-500 r / min; the drying temperature is 70-80° C., and the drying time is 2-3 h; and the pulverization is performed by using a jet mill to pulverize to a particle size of 0.2-0.5 μm.

5. The method for preparing modified titanium dioxide according to claim 1, characterized in that: In the step S2, the mass ratio of the composite powder to water is 1:(2-3).

6. The method for preparing modified titanium dioxide according to claim 1, characterized in that: In the step S2, the mass concentration of the sodium aluminate solution is 10-40 g / L, and the mass ratio of the composite slurry to the sodium aluminate solution is 1:(0.1-1).

7. The method for preparing modified titanium dioxide according to claim 1, characterized in that: In the step S2, the mass concentration of the sodium silicate solution is 20-60 g / L, and the mass ratio of the composite slurry to the sodium silicate solution is 1:(0.1-1).

8. A modified titanium dioxide, characterized in that: The modified titanium dioxide is prepared by the preparation method of any one of claims 1 to 8.

9. Use of the modified titanium dioxide according to claim 8 in the preparation of 3D printing ceramic materials.

Citation Information

Patent Citations

  • Method for preparing high water dispersibility titanium dioxide

    CN103965659A

  • Treatment method capable of improving weather resistance of titanium dioxide

    CN105062150A

  • Titanium dioxide with high weather resistance and preparation method thereof

    CN106947296A

  • Preparation method of titanium dioxide with high weather resistance and high coverage

    CN112538283A

  • Titanium dioxide with high weather resistance as well as preparation method and application thereof

    CN117624941A